A review of maximum power point tracking methods of PV power system at uniform and partial shading. (January 2016) - Liu, Liqun; Meng, Xiaoli; Liu, Chunxia
Abstract: The maximum power point tracking (MPPT) methods for the photovoltaic (PV) power system have been considered by the experts in the whole world. A review of different MPPT methods is discussed in this paper. Firstly, the main methods at uniform radiation that will be deliberated are Hill-Climbing (HC), Incremental Conductance (IncCond), Perturbation and Observation (P&O), Fuzzy-Logic (FL), and Neural Network (NN). However, these existing methods have several drawbacks such as slow tracking speed, low tracking efficiency, which fail to extract maximum power at complex partial shading. Then, the more recent MPPT methods at partial shading are discussed to find the best MPPT control strategy, such as the particle swarm optimization (PSO) algorithm, Cuckoo Search (CS) method, and Fibonacci line search scheme, etc. The advantages and shortcomings of abovementioned MPPT methods are compared to find the optimal MPPT during partial shading conditions. It is imagined that this article will be a source of valuable information for PV professionals to keep abreast with the latest progress in the PV power area, as well as for new researchers to get started on MPPT.